Molecular chaperones regulate p53 and suppress senescence programs - Sherman, Michael (2007)
Many types of cancer cells constitutively express major molecular chaperones at high levels. Recent findings demonstrate that specific depletion of individual chaperones, including various members of the Hsp70 family, small heat shock proteins, or VCP/p97, leads to activation of p53 pathway and subsequently triggers cellular senescence. Here we discuss a possibility that in cancer cells high levels of chaperones serve to keep the p53 signaling under control, thus allowing cancer cells to evade the default senescence and form tumors.